Medyczne oraz lingwistyczne konteksty rozważań nad leksemem język i jego potencjałem frazeologicznym - Horyń, Ewa; Olma, Marceli; Michalik, Mirosław (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2023)
The object of description in the following paper is the lexeme język. Linguistic analysis has been broadened by medical context, in which the author presents the content regarding the tongue as the first part of the digestive system, as a sense of taste, and finally, as vocal apparatus. For this purpose, the most important issues connected with the structure, physiology and pathology of the tongue have been presented. The second part of the discussion has been dedicated to the place of the noun język, along with its synonyms and derived forms in old and contemporary general Polish language, as well as dialects. The final part contains remarks on the functioning of the word język in Polish phraseology. This lexeme, as a polysemantic unit, happens to be the component of numerous petrified word combinations, whose meaning reflects the variety of references and contexts preserved in old and contemporary Polish culture.